Pengembangan Model Ontologi Pada Domain Oleh-Oleh Khas Bali - Putu Ardi Sudarmika; Ngurah Agus Sanjaya ER (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2024)
Bali's typical souvenirs not only represent a high cultural heritage but also serve as a primary attraction for tourists. However, detailed information on these souvenirs remains limited, making it challenging for users to choose. To enhance accessibility, the concept of representing Bali's souvenir data in ontology-based knowledge emerged. The aim is to provide references to tourists by regularly structuring an ontology model. Knowledge about Bali's souvenirs is represented using RDF in triple concepts of subject, predicate, and object, accessible through SPARQL. The development process employs the methodology methodology, encompassing specification, knowledge acquisition, conceptualization, integration, implementation, evaluation, and documentation phases. The outcome is an ontology model featuring 4 classes, 3 Object Properties, data properties, 34 ontographs, and 28 individuals or instances, offering regularly relevant information about Bali's souvenirs. This method utilizes Protégé 5.5.0 software and a search-based application for testing its efficacy.